(3CUhd GdeMGSHI GdYGeI hab GdeNWW GdeMGSHj GdhWfj (B/s - (3HhjYbhH, YHO GdcQjes ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 1999)
(3GdeMGSHI(B- (3GdejRGfjI(B- (3NGUjGJ GdeNWW GdhWfj ddeMGSHI(B- (3GdeDSSI GdJLGQjI(B- (3GdeDSSI GdUfGYjI(B- (3GdQSe Ydi GdbjeI GdeVGaI(B- (3GdYedjGJ GdeYdbI HGdCehGd GdTNUjI(B- (3MSGHGJ GdJSjjQ(B- (3GdGhQGb GdJLGQjI(B- (3eUGQja GdYGedjf hGdeUGQja GdedMbI(B- (3JUMjM GdGNWGA(B- (3GdWQjbI GdeQcRjI(B- (3CYeGd GdLQO(B- (3LOGhd GbaGd GdSfI GdeGdjI(B.s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdYGeIs; (3GdeNWW GdeMGSHjs